NILAI TAMBAH, PENGENDALIAN PERSEDIAAN BAHAN BAKU DAN PENDAPATAN USAHA PADA KUB BINA SEJAHTERA DI KELURAHAN KANGKUNG KECAMATAN BUMI WARAS KOTA BANDAR LAMPUNG - Kurnisa Ayi Pertiwi; Muhammad Irfan Affandi; Eka Kasymir (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2015)
Fish Processor in KUB Bina Sejahtera can increase the added value of products and income of group members. This research aimed to analyze added value, the raw materials inventory control and income of KUB Sejahtera. The number of respondent in this study was six members of KUB Bina Sejahtera.  This group produced fishes which were processed into various products such as food, meatballs, ekado,  fish lumpia, otak-otak, and piletan.  The researcher used analytical method such as Hayami Formula, the EOQ method and income theory.  Fish processor industry in KUB Bina Sejahtera provided added value greater than zero, the results of EOQ showed that the entire control supplies of raw materials had optimal point because it had a frequency of purchase of raw materials about 4 up to 29 times each month,.  Income resulting from spring rolls fish was Rp338.825,93, meatballs was Rp231.825,93, fish lumpia was Rp338.825,93, otak-otak was Rp2.159.423,93, and piletan was Rp27.526.363,64. Key words : added value, EOQ, income, fish processing, KUB